2020
DOI: 10.1002/humu.24101
|View full text |Cite
|
Sign up to set email alerts
|

Rapid exome sequencing and adjunct RNA studies confirm the pathogenicity of a novel homozygous ASNS splicing variant in a critically ill neonate

Abstract: Rapid genomic diagnosis programs are transforming rare disease diagnosis in acute pediatrics. A ventilated newborn with cerebellar hypoplasia underwent rapid exome sequencing (75 h), identifying a novel homozygous ASNS splice-site variant (NM_133436.3:c.1476+1G>A) of uncertain significance. Rapid ASNS splicing studies using blood-derived messenger RNA from the family trio confirmed a consistent pattern of abnormal splicing induced by the variant (cryptic 5′ splice-site or exon 12 skipping) with absence of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Health economics analyses performed for A058-ASNS demonstrated that an early diagnosis, enabled through rapid RNA diagnostics, reduced hospitalization costs by A$117,800. 7 Although not yet measured formally, there are significant cost benefits of this study related to additional diagnoses of 9 similarly affected family members and facilitation of preventative medicine. Of note, 41% of diagnoses were used for prenatal counseling with half of those cases intending to use the molecular diagnosis for preimplantation genetic diagnosis or screening, reducing both the significant emotional anxiety for parents related to recurrence risk and the lifetime financial cost of health services caring for children with severe genetic disorders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Health economics analyses performed for A058-ASNS demonstrated that an early diagnosis, enabled through rapid RNA diagnostics, reduced hospitalization costs by A$117,800. 7 Although not yet measured formally, there are significant cost benefits of this study related to additional diagnoses of 9 similarly affected family members and facilitation of preventative medicine. Of note, 41% of diagnoses were used for prenatal counseling with half of those cases intending to use the molecular diagnosis for preimplantation genetic diagnosis or screening, reducing both the significant emotional anxiety for parents related to recurrence risk and the lifetime financial cost of health services caring for children with severe genetic disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Short reads of ≤150 nucleotides (nt) regularly do not span multiple exons to unambiguously identify which isoform is affected by any identified aberrant splicing. Furthermore, mis-spliced reads often do not match the reference genome and can be filtered out, mis-aligned, and/or present at comparatively low levels because of nonsense-mediated decay (NMD), 3,7,8 an innate surveillance pathway targeting transcripts with a premature termination codon. 9 A further challenge arises for heterozygous variants for which normally spliced mRNA is transcribed from the allele in trans.…”
Section: Introductionmentioning
confidence: 99%
“…Six out of 38 studies on rare disorders identified the need for both pre-test and post-test genetic counselling. 7,11,128,137,174,180 Studies focusing on rare disorders had specific post-test genetic counselling considerations. When providing genetic consultation to families with infants or pediatric patients with rare disorders, genetic counselling is recommended to accompany early diagnosis.…”
Section: Rare Disordersmentioning
confidence: 99%
“…4,[8][9][10] This experience has also been echoed in individual case reports. 11,12 There is uncertainty, however, on whether the additional cost of providing increasingly faster test results is outweighed by reductions in other health care costs and increases in personal utility. This study evaluates the incremental costs and benefits associated with rapid (results turnaround time of 2 weeks) and ultra-rapid (results turnaround time of 3 days) genomic testing, with and without early initiation, relative to standard genomic testing using real-world hospital cost data and published evidence on the incremental monetary value of the benefits generated.…”
Section: Introductionmentioning
confidence: 99%